Developing and Implementing the Massachusetts Comprehensive Cancer Control Coalition Survivorship Summit - Stephenie C. Lemon, PhD; Marianne N. Prout, MD, MPH; Junaidah B. Barnett, PhD, MCH(N); Maureen Sullivan Flynn, MS (Preventing Chronic Disease, 2010)
Cancer survivors face numerous medical and psychosocial challenges, which the medical and public health systems are ill-equipped to deal with. In May 2008, the Massachusetts Comprehensive Cancer Control Coalition conducted a Survivorship Summit to elicit input from cancer survivors and professionals on developing system-level action plans for cancer survivorship issues. We describe how health care and public health professionals can implement similar events. Our results suggest that a cancer survivorship summit can be a valuable tool for cancer coalitions and advocacy organizations in determining survivorship agendas and action plans.